The Effect of using Vocabulary Self-collection Strategy on Students’ Reading Comprehension at SMK N 1 Pangkalan Kerinci - Tengku Zamrizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The aim of this research to find out the weather there is any significant difference between before and after the use vocabulary self-collection strategy on students’ reading comprehension. The design of the research is a Quasi Experimental Design Nonequivalent Pre-test and Post-test Group Design”. Two groups are served as an experimental group and the other one as compared group Two classes of SMK N 1 Pangkalan Kerinci first-year students make up the research participants. X1 Networking Computer Technique (28 students) served as experimental group 1 and X Accounting Major (28 students) served as experimental group 2. Cluster random sampling was applied. Using SPSS 21 version, the data were analyzed using the paired sample t-test and independent sample t-test formula. The result of the research The analysis showed by using paired sample t test formula. to was -6,669, higher than tt with df 27 in significant 5% and 1% (2.06 <6,669>2,78. Furthermore, it also can be seen that Sig. (2-tailed) or probabilities was 0.000 smaller than 0.05 (0.000<0.05). It means that Ho was rejected and Ha was accepted or there was a significant effect of using Vocabulary Self-collection strategy reading toward students’ reading comprehension of narrative text for experimental group 1. In short, Vocabulary Self-collection help the experimental groups to pay more attention to the target of learning, invest a higher level of ability and mental effort, and engage in a deeper cognitive processing